Globally Uniform Harmonized System Nomenclature? Waivers for Developing Countries and Membership Development: Situation 2017 - Weerth, Carsten (Dnepropetrovsk: University of Customs and Finance on Behalf of the Regional Office for Capacity Building & Regional Training Centre for the European Region of the World Customs Organization, 2017)
The Harmonized Commodity Description and Coding System (HS) is the most successful legally binding instrument of the World Customs Organization (WCO) with 156 contracting parties. More and more countries and economic regions are applying the HS nomenclature worldwide. But not all member states are applying the same version of the HS nomenclature. Developing countries are allowed to use another (earlier) version of the nomenclature according to article 4 HS, however the WCO does not define the term "developing countries". In the main section this paper discusses the term "developing countries" and examines the nomenclature application by HS member states and non-member states. It displays data from 2008 and 2017 on the positon of HS parties regarding the version of the nomenclature they apply and explains that not only developing nations are not applying the most actual HS 2017 nomenclature but also two advanced economies (Iceland and Singapore): 83 out of 156 contracting parties have successfully implemented the HS 2017 and 56 HS member states are still using older HS versions. Four contracting parties are planning to implement the HS 2017 in 2018 and one in 2019. 46 HS applicants are so called non-members and not HS member states in 2017. Three non-members are advanced economies (all three are WTO members): Hong Kong, Macao and Liechtenstein. The membership development of the HS is examined and future accessions are forecasted. This paper is researched by help of the WCO publications on the HS, the legal texts of the HS and the position of parties for the HS, the WCO publications for the signature and ratification of the Harmonised System Convention and by help of WTO publications on their membership and observers. The methods used during the study are analysis, synthesis, comparison, generalization, systematic and functional analysis.